Vector Competence of Thrips Species to Transmit Soybean Vein Necrosis Virus - Han, Jinlong; Nalam, Vamsi J.; Yu, I-Chen; Nachappa, Punya (Frontiers in Microbiology, 2019)
Soybean vein necrosis virus (SVNV) is a newly discovered species of tospovirus infecting soybean plants that is transmitted by the primary vector, soybean thrips, (Neohydatothrips variabilis), and two additional secondary vectors, tobacco thrips (Frankliniella fusca) and eastern flower thrips (F. tritici). This study was undertaken to elucidate the association between virus acquisition (6, 12, 24 and 48-h acquisition access period) and transmission efficiency (12, 24, and 48-h inoculation access period) in the primary vector, N. variabilis and to examine the mechanisms of vector competence by analyzing the effect of AAP (6, 12, 24-h) on virus infection in various tissues. In addition, we examined virus infection in tissues of the two secondary vectors. We found a significant effect of acquisition access period (AAP) on transmission efficiency, transmission rate post 6-h and 48-h AAP was significantly lower than 12-h and 24-h AAP. Our analysis did not reveal a correlation between virus transmission rate and virus RNA in corresponding N. variabilis adults. On the contrary, N. variabilis adults harboring higher accumulation of the virus (>104) resulted in lower transmission rates. Analysis of SVNV infection in the tissues revealed the presence of the virus in the foregut, midgut (region 1, 2 and 3), tubular salivary glands and primary salivary glands of adults of all three vector species; however the frequency of infected tissues was highest in N. variabilis followed by F. fusca and F. tritici. The frequency of SVNV infection in individual tissues specifically the salivary glands was lowest after 6-h AAP compared to 12-h and 24-h AAP. This finding is in agreement with the transmission assays, where significantly lower virus transmission rate was observed post 6-h AAP. In addition, N. variabilis adults with high primary salivary gland infection (12-h and 24-h AAP) were likely to have high percentage of foregut and midgut region 2 infection. Overall, results from the transmission assays and immunolabeling experiments suggest that shorter AAP results in reduced virus infection in the various tissues especially primary salivary glands, which probably important determinants of vector competence in SVNV-thrips interaction.